Capital policy of German savings banks: a survey - Volker Kleff (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
In contrast to earlier field studies, we survey German public savings banks on their management of capital. We find that the most important determinants of the savings banks? target capital ratio are risk aversion, the desired credit growth and profitability. Savings banks prefer to manage the level of capital rather than the level of riskweighted assets in order to reach their target capital ratio. The most important instruments to increase the level of capital are lowering costs and issuing subordinated debt. We obtain strong evidence that issuing subordinated debt is a particularly important instrument to increase capital for less capitalised savings banks.
Keywords: G21; 330; Capital; Savings Banks; Germany; Survey; Sparkasse; Bankbilanz; Bilanzstrukturmanagement; Schätzung; Deutschland